The association between blood MxA mRNA and long-term disease activity in early multiple sclerosis - Coerver, Eline M. E.; Strijbis, Eva M. M.; Petzold, Laura F.; Van Kempen, Zoé L. E.; Jasperse, Bas; Barkhof, Frederik; Oudejans, Cees B. M.; Uitdehaag, Bernard M. J.; Teunissen, Charlotte E.; Killestein, Joep (Frontiers in Neurology, 2022)
Background Myxovirus resistance protein A (MxA) is a protein that is upregulated by interferon-beta. Homeostatic MxA mRNA levels are potentially correlated with inflammatory disease activity in multiple sclerosis (MS) and could have an important role in MS pathology. Aim To investigate the association between myxovirus resistance protein A (MxA) mRNA levels in blood and disease activity and progression in MS over a long-term follow-up period. Methods Baseline blood MxA mRNA levels were determined in a prospective cohort of 116 untreated patients with a clinically isolated syndrome (CIS) or early relapsing remitting MS (RRMS), and related to long-term relapses, radiological disease activity, clinical scores [Expanded Disability Status Scale (EDSS), timed-25-foot walk (T25FW), 9-hole-peg test (9HPT)], MS type, and disease modifying therapy (DMT) use. Results Low MxA mRNA levels were associated with the occurrence of ≥9 T2-lesions on MRI imaging and the occurrence of relapses during long-term follow-up (median 11 years, IQR 5.91–13.69 years). MxA mRNA levels were not associated with EDSS, T25FW, 9HPT, and MS subtype. Conclusion Baseline MxA mRNA levels are associated with long-term development of T2-lesions on MRI-scans in our cohort. This confirms the relevance of the endogenous interferon-beta system in the occurrence of MS disease activity.